Dual-colour imaging of RNAs using quencher- and fluorophore-binding aptamers - Arora, Ankita; Sünbül, Murat; Jäschke, Andres (Nucleic acids research, 2015)
Abstract. In order to gain deeper insight into the functions and dynamics of RNA in cells, the development of methods for imaging multiple RNAs simultaneously
Gesehen am 28.07.2020